Hematopoietic or Osteoclast-Specific Deletion of Syk Leads to Increased Bone Mass in Experimental Mice - Csete, Dániel; Simon, Edina; Alatshan, Ahmad; Aradi, Petra; Dobó-Nagy, Csaba; Jakus, Zoltán; Benkő, Szilvia; Győri, Dávid S.; Mócsai, Attila (Frontiers in Immunology, 2019)
Syk is a nonreceptor tyrosine kinase critically involved in signaling by various immunoreceptors including B-cell-receptors and activating Fc-receptors. We have previously shown that Syk also mediates immunoreceptor-like signals required for the in vitro development and function of osteoclasts. However, the perinatal lethality of Syk–/– mice precluded the analysis of the role of Syk in in vivo bone metabolism. To overcome that problem, we generated mice with osteoclast-specific (SykΔOC) or hematopoietic (SykΔHaemo) Syk deficiency by conditional deletion of Syk using Cre recombinase expressed under the control of the Ctsk or Vav1 promoter, respectively. Micro-CT analysis revealed increased bone trabecular density in both SykΔOC and SykΔHaemo mice, although hematopoietic Syk deficiency caused a more severe phenotype than osteoclast-specific Syk deficiency. Osteoclast-specific Syk deficiency reduced, whereas hematopoietic Syk deficiency completely blocked in vitro development of osteoclasts. Both interventions inhibited the resorptive activity of osteoclasts and osteoclast-specific gene expression. Kinetic analysis of Syk protein levels, Cre expression and the genomic deletion of the Sykflox allele revealed complete and early deletion of Syk from SykΔHaemo osteoclasts whereas Syk was incompletely deleted at a later stage of osteoclast development from SykΔOC cultures. Those results provide an explanation for the in vivo and in vitro difference between the SykΔOC and SykΔHaemo mutant strains and suggest late activation of, and incomplete target gene deletion upon, osteoclast-specific Cre expression driven by the Ctsk promoter. Taken together, our results indicate that Syk plays an indispensable role in osteoclast-mediated in vivo bone resorption and suggest that Syk-specific inhibitors may provide therapeutic benefit in inflammatory and other diseases characterized by excessive osteoclast-mediated bone resorption.